"Reading" rights - Bakran, Juraj (Array, 2000)
The trend in the world is towards making public and academic libraries also accessible to the blind and visually impaired. With the technology we have great opportunity to make digital imformation accessible to the visually impaired. Suggested method is MBROLA diphone synthesis. MBROLA synthesiszer is a product of Faculte Polytechnique de Mons (Belgium). Croatian team joined the project, providing their Croatian diphone database to be used with MBROLA synthesizer.